IDENTIFIKASI FAKTOR PENCEGAHAN WASTE PADA SUPPLY CHAIN MANAGEMENT DENGAN PENDEKATAN LEAN PADA PROYEK KONSTRUKSI - Yudiawan, Muhammad Satria; Raflis, Raflis (Universitas Pendidikan Indonesia (UPI), 2025)
The rapid growth of urbanization drives the rapid physical growth of cities to stabilize the balance between needs and population growth. The construction industry plays a crucial role in the physical development of cities by building infrastructure. However, there are challenges in infrastructure development, one of which is waste. The lean approach enhances value for customers by eliminating waste in processes and resources. This study aims to identify and analyze the factors that prevent waste in supply chain management in construction projects and to evaluate the influence of these variables on the implementation of LSCM. The research method used in this study is quantitative, with data collected through a questionnaire distributed to 53 respondents involved in supply chain management, including contractors and consultants. The data obtained were processed using IBM SPSS version 29.0 for multiple linear regression analysis. The analysis results indicate that the variables of Operations and Purchasing and Procurement have a significant impact on the implementation of LSCM in reducing waste, with Asymp. Sig. values of 0.033 and 0.003, respectively. Meanwhile, the variables of Integration, Distribution, and Logistics did not show a significant impact. The F-test indicates that simultaneously, all independent variables significantly affect the dependent variable, with a calculated F value of 12.323. The R-squared value obtained is 0.507, indicating that 50.7% of the variation in the implementation of LSCM can be explained by the independent variables studied.Keywords: Construction, Lean Thinking, Supply Chain Management, Sustainable Development, Waste